Establishment of new fitted geoid model in Universiti Teknologi Malaysia - Muhammad Khairulfalah Ismail, 1995-, author 613540 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2018